Thương hiệu OCOP giả xanh có khiến khách hàng quay lưng? Nhận thức tẩy xanh và ý định tẩy chay thương hiệu dưới góc nhìn bản sắc môi trường - Trần Hải, Ly; Lại Minh, Sang; Nguyễn Kim , Thảo; Nguyễn Đình Thùy, Linh; Nguyễn Minh, Phương; Phạm Thị Chúc, An (JOURNAL OF ASIAN BUSINESS AND ECONOMIC STUDIES, 2025)
In the context where green communication is increasingly adopted in the marketing activities of enterprises participating in the “One Commune One Product” (OCOP) program, the phenomenon of greenwashing poses a significant challenge to consumer trust. This study aims to explore the relationships among greenwashing perception, environmental self-identity, and boycotting intention, and to examine the moderating role of environmental self-identity. Based on the theoretical foundation, the authors developed a conceptual model and conducted a survey of 191 consumers in Vietnam. Using Partial Least Squares Structural Equation Modeling (PLS-SEM), the results indicate that: (1) environmental self-identity positively affects greenwashing perception; (2) greenwashing perception has a significant influence on brand boycotting intention; and (3) environmental self-identity moderates the relationship between greenwashing perception and brand boycotting intention, in a way that intensifies consumers’ reactions. These findings provide empirical evidence of the socio-psychological mechanisms underlying consumer responses to misleading green communication. The practical implications highlight the need for enterprises to ensure transparency in their communication, build a credible environmental identity, and avoid exaggerating green commitments. At the same time, regulatory authorities should strengthen monitoring and certification mechanisms to protect a sustainable communication ecosystem within the OCOP program.